2013
DOI: 10.1007/s12032-013-0608-6
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic relationship between dipeptidyl peptidase IV and neutral endopeptidase expression and the combined prognostic significance in osteosarcoma patients

Abstract: Neutral endopeptidase (NEP/CD10) and dipeptidyl peptidase IV (DPP IV/CD26) are both ubiquitous glycopeptidases which play important roles in tumor pathogenesis and development. The aim of this study was to investigate the expression patterns and the prognostic significance of CD10 and CD26 in osteosarcoma patients. CD10 and CD26 expression in 116 pairs of primary osteosarcoma and corresponding noncancerous bone tissue samples from the same specimens were detected by immunohistochemistry. The Spearman's correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…After that, the protein was visualized by DAB staining. Moreover, the degree of immunostaining was evaluated based on the percentage of positive tumor cells and the intensity of staining by two observers independently according to the methods described previously (Zhang et al 2013). The percentage scoring of immunoreactive tumor cells was: 0 (no positive tumor cells), 1 (< 10% positive tumor cells), 2 (10% to 50% positive tumor cells) and 3 (> 50% positive tumor cells).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…After that, the protein was visualized by DAB staining. Moreover, the degree of immunostaining was evaluated based on the percentage of positive tumor cells and the intensity of staining by two observers independently according to the methods described previously (Zhang et al 2013). The percentage scoring of immunoreactive tumor cells was: 0 (no positive tumor cells), 1 (< 10% positive tumor cells), 2 (10% to 50% positive tumor cells) and 3 (> 50% positive tumor cells).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…In osteosarcoma, VEGF is a pro-angiogenic factor with a key role in pulmonary metastasis and poor prognosis [25,26]. The expression of PDGF-AA, endostatin, endothelin-1 and CD26 has been previously shown to be positively correlated with tumor progression in osteosarcoma [27,28,29,30] and the upregulation of serpin E1 and thrombospondin-1 in OS cells has been correlated with an increased risk of lung metastasis [31,32]. Additionally, Endo-Munoz L. et al, suggested an association between the metastatic behavior of OS and the activation of uPA axis carried by EVs at distant sites [33].…”
Section: Discussionmentioning
confidence: 99%
“…22 However, further studies are needed to clarify the potential correlations between ABO blood type, CD26 expression, and pancreatic diseases. Unlike in other cancers, 8,[25][26][27] in pancreatic malignancies, the expression status of CD26 was not associated with DFS or OS, which may be attributed to the high positive rate. However, when patients were classified into CD26 high-/low-expression groups, higher CD26 expression was correlated with poorer DFS and OS and was an independent predictive factor of OS.…”
Section: Discussionmentioning
confidence: 58%